Desa Bebas Hipertensi: Sinergi Edukasi dan Pemeriksaan Kesehatan Berbasis Masyarakat di Desa Badalpandean Kecamatan Ngadiluwih Kabupaten Kediri - Radono, Panca; Natalia, Shanty; Maramba, Martinus; Mufidah, Nida Azhar; Araujo, Feliciano De; Daik, Jelli; Salma, Adevia; Laluna, Laila; Fitria, Henik Nur; Firdaus, Tsabitah Putri; Wardana, Ica Putri; Padaka, Serli Alisa; Kaka, Mersiana Ambu (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Hypertension is one of the most common non-communicable diseases affecting the community, especially the elderly. The prevalence of hypertension in Indonesia is quite high, but many cases go undiagnosed. Low public knowledge and awareness of risk factors and hypertension prevention poses a challenge, particularly in rural areas. Objective: The purpose of this service was increase public knowledge and awareness, particularly among women and the elderly in Badalpandean Village, regarding hypertension, its risk factors, and prevention, and to motivate residents to undergo regular health check-ups. Method: The activity was conducted in Badalpandean Village, targeting women and the elderly. Methods used included health education about hypertension using leaflets, blood pressure measurement simulations, and knowledge evaluation through pre- and post-tests. Additionally, blood pressure, random blood sugar (ABG), and uric acid levels were checked for early detection. Result: A total of 24 participants participated in the activity, the majority of whom were women (96%) and aged 51–70 years. Pre-test results showed that 16.67% of participants had"poor" knowledge, 62.5% had "fair" knowledge, and 20.83% had "good" knowledge. After education, 62.5% of participants were in the "good" category, and no participants were in the poor" category. Conclusion: The combination of education and community-based health examinations effectively increased community awareness and knowledge about hypertension. This strategy can be used as a model for similar interventions in other areas for hypertension prevention and control at the village level.